2012
DOI: 10.5194/amt-5-17-2012
|View full text |Cite
|
Sign up to set email alerts
|

Ground-based water vapor raman lidar measurements up to the upper troposphere and lower stratosphere for long-term monitoring

Abstract: Abstract. Recognizing the importance of water vapor in the upper troposphere and lower stratosphere (UTLS) and the scarcity of high-quality, long-term measurements, JPL began the development of a powerful Raman lidar in 2005 to try to meet these needs. This development was endorsed by the Network for the Detection of Atmospheric Composition Change (NDACC) and the validation program for the EOSAura satellite. In this paper we review the stages in the instrumental development, data acquisition and analysis, prof… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 26 publications
(25 reference statements)
2
86
0
Order By: Relevance
“…C is obtained as the average value of the ratio between the uncalibrated RL ( ) profile and the ( ) profile from over the height-range from 1.5 to 3.5 km a.s.l. (Guerrero-Rascado et al, 2008b;Leblanc et al, 2012;Navas-Guzmán et al 20 2014;Foth et al, 2015). C remains constant over periods when the lidar setup is not modified and the system presents good alignment, allowing us to retrieve ( ) profiles from the RL even when RS measurements are not available.…”
Section: Slope I Field Campaignmentioning
confidence: 99%
“…C is obtained as the average value of the ratio between the uncalibrated RL ( ) profile and the ( ) profile from over the height-range from 1.5 to 3.5 km a.s.l. (Guerrero-Rascado et al, 2008b;Leblanc et al, 2012;Navas-Guzmán et al 20 2014;Foth et al, 2015). C remains constant over periods when the lidar setup is not modified and the system presents good alignment, allowing us to retrieve ( ) profiles from the RL even when RS measurements are not available.…”
Section: Slope I Field Campaignmentioning
confidence: 99%
“…Raman-scattering-based lidar for atmospheric water vapor measurements has been amply described in the literature (Mel, 1972;Sherlock et al, 1999b;Leblanc et al, 2012). However, to discuss the adopted technical solutions in the system configuration of RMR-H 2 O, it is useful to report the equation relating the water vapor mixing ratio (WVMR, w in the equation) to the recorded Raman signals:…”
Section: Raman Lidar Wv Profile Retrievalmentioning
confidence: 99%
“…To optimize the Raman lidar technique to water vapor measurements, it is necessary to quantify the systematic biases affecting the technique. In particular, several studies (Sherlock et al, 1999;Ferrare et al, 2004;Whiteman et al, 2006;Leblanc et al, 2012) have highlighted that many lidar systems experienced an excess amount of water vapor (wet bias) in the mid-upper troposphere lidar profile, significantly impacting their measurements. The recent work of Whiteman et al (2012) identified three general causes for this effect: (1) instrumental effects, (2) data processing, (3) atmospheric constituents.…”
Section: Rejection Of the Residual Signalsmentioning
confidence: 99%
See 2 more Smart Citations